Against dogmatism : dwelling in faith and doubt - Yadlapati, Madhuri M. (Urbana [Illinois] : University of Illinois Press, 2013)
Defending the rich tapestry of faith and doubt against polarisation, 'Against Dogmatism' reveals a spiritual middle way, an approach native to the long-standing traditions in which faith and doubt are interwoven in constructive and dynamic ways.
Introduction : beyond fundamentalism and atheism -- Part 1. Re-examining faith in action. Postures of trust -- What is our sacred responsibility in the world? -- Part 2. The centrality of doubt. Christian faith and the Protestant principle -- Faith and transcendence in Hindu traditions -- Part 3. Reconciling ways of faith and doubt. Resisting the reification of religion -- Faith and hope for the twenty-first century -- Conclusion : dwelling in uncertainty.
Includes index.
Print verison record.
Includes bibliographical references (pages 175-195) and index.
English.
eBooks on EBSCOhost
Keywords: Faith -- Meditations; Belief and doubt -- Religious aspects; Philosophy and religion -- History; Foi -- Méditations.; Croyance et doute -- Aspect religieux; BODY, MIND & SPIRIT -- Gaia & Earth Energies; RELIGION -- Christianity -- General; RELIGION -- Theology; PHILOSOPHY -- Religious; Faith; Philosophy and religion; Electronic book; History; Meditations